2018
DOI: 10.1371/journal.pone.0194868
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV pathogenesis and antiviral efficacy of licensed drugs in human monocyte-derived antigen-presenting cells

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) presents an emerging threat to public health worldwide by causing severe respiratory disease in humans with high virulence and case fatality rate (about 35%) since 2012. Little is known about the pathogenesis and innate antiviral response in primary human monocyte-derived macrophages (MDMs) and dendritic cells (MDDCs) upon MERS-CoV infection. In this study, we assessed MERS-CoV replication as well as induction of inflammatory cytokines and chemokines in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 43 publications
5
93
0
3
Order By: Relevance
“…Toremifene, Chlorpromazine, and Chloroquine were evaluated using Vero cells, human monocyte-derived macrophages (MDMs) and immature dendritic cells (MDDCs) [41]. These drugs were transferred to cells 1 h prior to infection with MERS-CoV.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Toremifene, Chlorpromazine, and Chloroquine were evaluated using Vero cells, human monocyte-derived macrophages (MDMs) and immature dendritic cells (MDDCs) [41]. These drugs were transferred to cells 1 h prior to infection with MERS-CoV.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Toremifene reduced virus by 1-1.5 log10 at a dose more than 20 ÎźM. Chlorpromazine reduced MERS-CoV by 2 log10 and had a narrow therapeutic window and a high toxicity [41]. Chloroquine, Chloropromazine, and loperamide were tested on Huh7 cells [43].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Coronaviruses are single-stranded positive-sense RNA viruses (Zumla et al 2015), with human pathogenic strains resulting in a common cold to a severe acute respiratory syndrome (CastaĂąo-Rodriguez et al 2018). MERS-CoV, an emerging zoonotic virus (Alamoudi et al 2018;Cong et al 2018) is pathogenic in human, resulting in shortness of breath, cough, fever, diarrhea, and frequently pneumonia (Cong et al 2018;Sherbini et al 2017). The exact animal origin of MERS-CoV is not fully understood, but the transmission pattern and the evidence from virologic studies suggest that it may have originated in bats and was transmitted to camels sometime in the distant past (Hu et al 2015, Wang et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…This was accompanied by initial steps of viral infection and replication, evidenced by increased N protein RNA in infected cells, but not by productive replication or viral amplification . Recent studies suggested that while mature MDDCs did not seem to be permissive to MERS-CoV infection, immature MDDCs were permissive but, unlike with macrophages, infection in vitro did not result in up-regulation of proinflammatory cytokine and chemokine production (Cong et al, 2018). As dendritic cells enter peripheral tissues and carry antigens to lymphoid tissues, it has been suggested that they may contribute to MERS-CoV dissemination by acting as vehicles, possibly explaining the isolation of MERS-CoV from specimens other than respiratory tract samples such as blood, stool, and urine from MERS-CoV infected patients Guery et al, 2013).…”
Section: Mers-cov Virus Infects and Replicates In Human Macrophagesmentioning
confidence: 99%